2012
DOI: 10.1111/chd.12010
|View full text |Cite
|
Sign up to set email alerts
|

Restrictive Lung Disease is an Independent Predictor of Exercise Intolerance in the Adult with Congenital Heart Disease

Abstract: Background/Objectives Following repair of congenital heart disease (CHD), adult patients are at risk for reduced exercise capacity. Restrictive lung disease (RLD) may contribute to reduced exercise capacity in this population. The aim of this study was to determine the prevalence of RLD and its impact on exercise tolerance in the adult with congenital heart disease. Methods One hundred consecutive adult patients with CHD, who underwent routine cardiopulmonary exercise testing with spirometry, were evaluated.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(62 citation statements)
references
References 29 publications
1
59
1
1
Order By: Relevance
“…The reported association between abnormal spirometry and mortality, in conjunction with previous reports relating abnormal FVC to lower aerobic capacity, 6 lends importance to the high prevalence of low FVC in this population. Although this is the first report to specifically highlight this connection among adults with congenital heart disease, numerous studies have reported an association between spirometric variables (eg, slow vital capacity, FEV 1 , and FVC) and overall and cardiovascular mortality both in patients with acquired heart disease and in the general population, independent of tobacco use or clinical lung disease.…”
Section: February 26 2013mentioning
confidence: 52%
See 1 more Smart Citation
“…The reported association between abnormal spirometry and mortality, in conjunction with previous reports relating abnormal FVC to lower aerobic capacity, 6 lends importance to the high prevalence of low FVC in this population. Although this is the first report to specifically highlight this connection among adults with congenital heart disease, numerous studies have reported an association between spirometric variables (eg, slow vital capacity, FEV 1 , and FVC) and overall and cardiovascular mortality both in patients with acquired heart disease and in the general population, independent of tobacco use or clinical lung disease.…”
Section: February 26 2013mentioning
confidence: 52%
“…6,7 Although the present report includes a large number of patients, available pulmonary function data are limited to simple spirometry without information on lung volumes or diffusing capacity, which limits mechanistic inference. Previous reports demonstrated that the pattern of pulmonary function abnormalities and underlying mechanisms may vary between defects and at different stages of disease and repair.…”
Section: Article See P 882mentioning
confidence: 99%
“…58 Forty-four percent of adults with CHD demonstrated a pattern on spirometry suggestive of restrictive lung disease, which is markedly higher than the 9% prevalence in the general adult population. 59 The prevalence of restrictive lung disease was highest in patients with a history of Fontan procedure (89%) and tetralogy of Fallot (TOF) repair (76%). 59 Forced vital capacity and forced expiratory volume in 1 second have been shown to be reduced in adults with CHD, a finding that is highly suggestive of abnormal pulmonary mechanics.…”
Section: Lung Prevalencementioning
confidence: 97%
“…Nearly half (44-47%) of ACHD patients have restrictive lung disease (RLD), including 89% following Fontan repair and 76% with TOF [31,32]. Predictors of RLD include multiple prior thoracotomies (possibly due to associated chest wall deformity or weakness), diaphragmatic nerve palsy, cardiomegaly, atrial arrhythmias (perhaps related to amiodarone use), scoliosis, complex CHD, and increased BMI [32,33].…”
Section: Pulmonary Function Limitationsmentioning
confidence: 99%